2019
DOI: 10.1158/1535-7163.mct-18-0582
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Somatic Mutations Affecting Receptor Tyrosine Kinase Family in Metastatic Colorectal Cancer

Abstract: Besides the detection of somatic receptor tyrosine kinases (RTK) mutations in tumor samples, the current challenge is to interpret their biological relevance to give patients effective targeted treatment. By high-throughput sequencing of the 58 RTK exons of healthy tissues, colorectal tumors, and hepatic metastases from 30 patients, 38 different somatic mutations in RTKs were identified. The mutations in the kinase domains and present in both tumors and metastases were reconstituted to perform an unbiased func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…EphA4 activation contributes to the aggressive phenotype and therapeutic resistance in CRC. Although mutations in EPHA4 have not caused inhibition of its kinase activity ( 99 ), previous studies have suggested a role for this receptor in disease pathogenesis. Overexpression of EPHA4 is associated with promotion of liver metastasis ( 42 ) ( Table 1 ).…”
Section: Epha Receptorsmentioning
confidence: 99%
“…EphA4 activation contributes to the aggressive phenotype and therapeutic resistance in CRC. Although mutations in EPHA4 have not caused inhibition of its kinase activity ( 99 ), previous studies have suggested a role for this receptor in disease pathogenesis. Overexpression of EPHA4 is associated with promotion of liver metastasis ( 42 ) ( Table 1 ).…”
Section: Epha Receptorsmentioning
confidence: 99%